Sosialisasi Strategi Bisnis Bagi UMKM di Era Now Normal Desa Suka Mulia Kec Pagar Merbau Kab Deli Serdang - M Dani Habra; Junita Putri Rajana Harahap (Forum Kerjasama Pendidikan Tinggi, 2021)
The Pandemic period due to Covid-19 had a negative impact on people's lives, especially from the economic side of the family. To solve the covid-19 problem, the Government recommends doing social distancing for all Indonesian people. People are required to always maintain their health through the use of masks, hand sanitizers and always maintain personal hygiene. The government is working with the University in helping the community through the Community Service Program (Mandiri) - Learning to Care for Covid 19. This activity is held for 5 weeks in which students go directly to the community. This program is implemented in Sukamulia Village, Pagar Merbau District, Deli Serdang Regency, which consists of two hamlets. The work program carried out includes providing counseling and assistance in terms of developing local community businesses or industries through appropriate business strategies and providing counseling on how to maintain health in the face of the Covid-19 virus